2013
DOI: 10.1016/j.bbamem.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and phase specificity of α-toxin from S. aureus

Abstract: The pore forming toxin Hla (α-toxin) from Staphylococcus aureus is an important pathogenic factor of the bacterium S. aureus and also a model system for the process of membrane-induced protein oligomerisation and pore formation. It has been shown that binding to lipid membranes at neutral or basic pH requires the presence of a phosphocholine-headgroup. Thus, sphingomyelin and phosphatidylcholine may serve as interaction partners in cellular membranes. Based on earlier studies it has been suggested that rafts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…We have previously shown that, like other bacterial toxins, e.g., (Alonso et al , 2000; Boesze-Battaglia et al , 2009; Farrand et al , 2010; Lai et al , 2013; Maxfield and Tabas, 2005; Patel et al , 2002; Schwiering et al , 2013; Zitzer et al , 2001), LtxA requires cholesterol in the plasma membrane to bind and kill target cells (Brown et al , 2013; Brown et al , 2015; Fong et al , 2006). Thus, it is possible that the cell counteracts DRAQ5 ™ -mediated decreases in the plasma membrane fluidity by decreasing the membrane cholesterol composition and that this change inhibits LtxA internalization.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that, like other bacterial toxins, e.g., (Alonso et al , 2000; Boesze-Battaglia et al , 2009; Farrand et al , 2010; Lai et al , 2013; Maxfield and Tabas, 2005; Patel et al , 2002; Schwiering et al , 2013; Zitzer et al , 2001), LtxA requires cholesterol in the plasma membrane to bind and kill target cells (Brown et al , 2013; Brown et al , 2015; Fong et al , 2006). Thus, it is possible that the cell counteracts DRAQ5 ™ -mediated decreases in the plasma membrane fluidity by decreasing the membrane cholesterol composition and that this change inhibits LtxA internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Lending support to the former mechanism, (1) α-toxin binds to artificial lipid membranes, and can perforate lipid vesicles leading to the release of intravesicular contents [52,66,83,84,85,86,87,88,89]; (2) the “rim-stem crevice” of the toxin directly interacts with membrane lipids [90]; (3) cholesterol depletion abrogates binding of α-toxin to host cell membranes [82]; and (4) the addition of exogenous phosphocholine antagonizes toxin binding [82]. Further, multiple bacterial pore-forming cytotoxins utilize membrane lipids as their cellular receptors establishing a precedent for this mode of interaction [91].…”
Section: Properties Of α-Toxinmentioning
confidence: 99%
“…Cell death induced by S. aureus is primarily mediated by secretion of alpha toxin (Bubeck Wardenburg et al , 2007; Taubler et al , 1963), a destructive pore-forming toxin that is often found in the lesions of patients with severe AD (Travers et al , 2001; Wichmann et al , 2009). Alpha toxin induced cell lysis requires that the host express the lipid, sphingomyelin, on its cell surface (Schwiering et al , 2013; Watanabe et al , 1987). It has been reported that alpha toxin specifically recognizes the phosphocholine head group of sphingomyelin (Valeva et al , 2006).…”
Section: Introductionmentioning
confidence: 99%